Packet loss rate of an optical burst switch with nonlinear optical loop mirrors - Tang, M. F.; Abbou, F. M.; Abid, A.; Mishra, V. N.; Chuah, Hean Teik (The Institute of Electronics, Information and Communication Engineers, 2006)
Optical Burst Switching (OBS) is designed to efficiently exploit the enormous bandwidth offered by the optical fiber. Contention is one of the major problems in the deployment of OBS networks. In this paper, a new contention resolution method is introduced. This method is based on the burst segmentation scheme and the use of Nonlinear Optical Loop Mirrors (NOLMs). The NOLMs are incorporated with SOA to provide optical buffering and ultra-fast optical switching services to the segmented bursts. Furthermore, the introduced method is evaluated in term of the packet loss rate versus various traffic loads with Pareto distributed and negative-Exponentially distributed burst length.